Wybrane problemy procesu rekrutacji do służby cywilnej - Pakuła, Andrzej (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The quality of public administration significantly depends on the quality of its personnel. Personnel should be treated as significant resource (capital). The main element of this capital are hard skills and soft skills.
Keywords: public administration; civil service; human resource (human capital); skills